Initiating structural studies of Lys49-PLA2 homologues complexed with an anionic detergent, a fatty acid and a natural lipid - Watanabe, L.; Fontes, MRM; Soares, A. M.; Giglio, JR; Arni, R. K. (Bentham Science Publ Ltd, 2003)
Lys49-Phospholipase A(2) (Lys49-PLA(2) - EC 3.1.1.4) homologues damage membranes by a Ca2+-independent mechanism which does not involve catalytic activity. Both MjTX-II from Bothrops moojeni and BthTX-I from Bothrops jararacussu are dimeric in solution and in the crystalline states, and a model for the Ca2+-independent membrane damaging mechanism has been suggested in which flexibility at the dimer interface region pert-nits quaternary structural transitions between open and closed membrane bound dimer conformations which results in the perturbation of membrane phospholipids and disruption of the bilayer structure [1]. With the aim of gaining insights into the structural determinants involved in protein/lipid association, we report here the crystallization and preliminary X-ray analysis of the (i) MjTX-II/SDS complex at a resolution of 2.78Angstrom, (ii) MjTX-II/STE complex at a resolution of 1.8 Angstrom and (W) BthTX-I/DMPC complex at 2.72Angstrom. These complexes were crystallized by the hanging drop vapour-diffusion technique in (i) HEPES buffer (pH 7.5) 1.8M ammonium sulfate with 2% (w/v) polyethyleneglycol 400, in (ii) 0.6-0.8 M sodium citrate as the precipitant (pH 6.0-6.5) and in (iii) sodium citrate buffer (pH 5.8) and PEG 4000 and 20% isopropanol, respectively. Single crystals of these complexes have been obtained and X-ray diffraction data have been collected at room temperature using a R-AXIS IV imaging plate system and graphite monochromated Cu Kalpha X-ray radiation generated by a Rigaku RU300 rotating anode generator for (i) and (W) and using using a Synchrotron Radiation Source (Laboratorio Nacional de Luz Sincrotron, LNLS, Campinas, Brazil) for (ii).
Keywords: phospholipase A(2); like-phospholipase; myotoxicity; crystallization; anionic detergent; fatty acid; natural lipid; Bothrops moojeni; Bothrops jararacussu